SISTEM DISTRIBUSI PUPUK BERSUBSIDI KE KELOMPOK TANI DI DESA TELANG MAKMUR KECAMATAN MUARA TELANG KABUPATEN BANYUASIN - Ependy, Arif; Abubakar, Rafeah (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2020)
The objective of this research were to factors that influence the decision of tidal paddy farmers to adopst ciherang varieties in Pulau Borang Village Banyuasin I district Banyuasin district from April to June 2019.  The research method used is the (case study) method. the sampling in  research this is the Disproportionate Stratified Random Sampling (unbalanced random). The sample farmers in this study were 68 sample farmers namely 34 strata I sample farmers of rice farmers who still adopted ciherang varieties and 34 strata II sample farmers were 34 farmers, namely farmers who adopted non-ciherang varieties. Data collection methods to obtain primary data while secondary data are obtained from extension services data management methods and data analysis using logictic regression with SPSS 20,0 software tools and quantitative descriptive results of the analysis of logistic models with the level 95 %, continue to adopt ciherang varieties simultaneously are influenced by land area, production costs, age, experience and income. Of the partially the factors that influence the decision of tidal rice farmers to adopt ciherang varieties are age, experience and income